Challenges, alternatives, and paths to sustainability: better public health promotion using social networking pages as key tools - Zaidan , A. A.; Zaidan , B. B.; Kadhem, Z.; Moussa, Larbani; Lakulu, Modi B.; Hashim, M. (Springer New York LLC, 2015)
This paper discusses the possibility of promoting public health and implementing educational health services using Facebook. We discuss the challenges and strengths of using such a platform as a tool for public health care systems from two different perspectives, namely, the view of IT developers and that of physicians. We present a new way of evaluating user interactivity in health care systems from tools provided by Facebook that measure statistical traffic in the Internet. Findings show that Facebook is a very promising tool in promoting e-health services in Web 2.0. Results from statistical traffic show that a Facebook page is more efficient than other pages in promoting public health.